CORDIC: Novel sequential and Pipelined Architectures and Performance issues - Ali, Usman; Sheikh, Umair Ali (Proceedings of INMIC 2005 9th International Multitopic Conference : December 23-24, 2005, 2005)
This paper presents a novel and simple sequential design of CORDIC for the calculation of Sine and Cosine of an angle. Design reduces the hardware requirement by using a single adder/subtrator module for all the iterations and for both Sine and Cosine calculation. Sequential design is implemented and synthesized in MAX plus 2 and time diagram is presented A parallel extension is also discussed, which would increase the speed Performance of the proposed design is compared with other general architectures available.